THE USE OF IMMUNOMODULATORS, BIOLOGIC THERAPIES AND SMALL MOLECULES IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE AND SOLID ORGAN TRANSPLANTS. (26th January 2023) - Ghusn, Wissam; Francis, Fadi; Farraye, Francis; Hashash, Jana G
Abstract: INTRODUCTION: Over the past 20 years, the number of solid organ transplants (SOT) for a variety of indications has been on the rise. Consequently, more patients with inflammatory bowel diseases (IBD) are also receiving SOT. Although SOT related immunosuppression may at times control IBD related inflammation, many patients still require additional immunosuppressive medications for control of their IBD. With the growing therapeutic armamentarium for IBD, physicians are in search for guidance on the safety of using additional immunosuppressive medications in patients who are already receiving transplant related immunosuppressive medications. METHODS: We performed a review of published literature that addressed the use of immunomodulators, biologic agents, and small molecules in patients with IBD who also had a SOT. We searched PubMed, Scopus, MEDLINE, and Google Scholar databases for studies published on the topic in English between January 1 st, 1910, and August 1 st, 2022. We have included data from systematic reviews, meta-analyses, case reports and case series to assess the safety, effectiveness, and side effects of immunomodulators, biologic therapies and small molecules in patients with liver, renal and/or heart transplantations. RESULTS: We identified 25 publications on liver transplants, 6 on renal transplants, and 1 on heart transplants in patients with IBD. Among liver transplant patients, the most common immunosuppressive medications used were tacrolimus, mycophenolate mofetil, cyclosporine and steroids. In patients with IBD, anti-TNF agents (infliximab and adalimumab) were used in SOT with no major adverse safety concerns. The most common adverse events included infections (Clostridioides difficile and CMV) and malignancies (colon cancer). As for anti-integrin agents (vedolizumab and natalizumab) and ustekinumab, their efficacy and safety were mainly reported in patients with liver transplant on tacrolimus with no major adverse events reported. For patients with renal transplant, the main immunosuppression used were cyclosporine and tacrolimus. The combination of these immunosuppressive drugs with either anti-TNF therapy or ustekinumab had a good safety profile with rare malignancy occurrence. In one case report with heart transplant in a patient with IBD and on tacrolimus, no complications were reported. CONCLUSION: SOT has become the mainstay for treating several common diseases. As such, gastroenterologists will care for more patients with IBD who have had a SOT. From this extensive review, the use of anti-TNF, anti-integrin agents and ustekinumab seem to be safe in patients with SOT, regardless of their transplant related immunosuppression which is usually comprised of tacrolimus, cyclosporine, and prednisone. More studies are needed in patients with renal and heart transplant and in patients treated with small molecules for their IBD.